Alkali-activated cement using slags and fly ash - Rios, S (2018)
Alkali Activated Cements (AAC) are a very convenient alternative to common binders as waste materials like slag and fly ash are included in their production. In this paper, a response surface method is used to optimize an AAC made with fly ash, steel slag, sodium silicate and sodium hydroxide. For this purpose, an experimental plan contemplating 26 mixtures was developed, which included compression and flexural strength tests. The experimental data was then analyzed using regression analysis and ANOVA. The results indicate that the sodium hydroxide/sodium silicate solution ratio is the most relevant variable, followed by the ratio between the two solid components (slag and fly ash).